SUSTAINABILITY STATUS OF MANGROVE ECOSYSTEM MANAGEMENT IN SEMBILANG NATIONAL PARK, BANYUASIN REGENCY, SOUTH SUMATERA PROVINCE - . Theresia; Mennofatria Boer; Niken T.M Pratiwi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
he utilization of mangrove in Sembilang National Park area has increased lately so that it is necessary to assess the sustainability of the mangrove ecosystem management in the region. The study was conducted in March-April 2015. The research location was in the National Park Sembilang, Banyuasin Regency, South Sumatra. The study used primary data and secondary data collections. The primary data were collected from direct observation of mangrove vegetation and via directs interviews of 86 respondents using purposive sampling method. The sustainability status and recommendations for management strategies were determined using Multi Dimensional Scaling (MDS) method approaching by RAPFISH (Rapid Assessment Technique for Fisheries).Current sustainabilitystatus of mangrove management in Sembilang National Park, Banyuasin Regency, South Sumatra was